USING ANTI-SYMMETRICAL PONYMS IN SOLVING ELEMENTARY MATHEMATICS PROBLEMS - Ummatova Mahbuba Axmedovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article discusses symmetric polynomials in the polynomial theory section of the algebra and number theory course, a class of polynomials very close to symmetric polynomials - antisymmetric polynomials and some of their applications to elementary mathematics.